Selected Topics on Archaeology, History and Culture in the Malay World (Springer Singapore, 2018)
This book presents selected academic papers addressing five key research areas - archaeology, history, language, culture and arts - related to the Malay Civilisation. It outlines new findings, interpretations, policies, methodologies and theories that were presented at the International Seminar on Archaeology, History, and Language in the Malay Civilisation (ASBAM5) in 2016. Further, it provides new perspectives and serves as a vital point of reference for all researchers, students, policymakers and legislators who have an interest in the Malay Civilisation.